FR1.3: Gendered differences in accessing and using climate-smart agricultural technologies in Tanzania - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu; Mutua, Mercy M.; Waswa, Boaz Shaban; Ndunguru, Agness; Kabungo, Catherine; Katunzi, Adolph; Nyamolo, Victor (Bioversity International and the International Center for Tropical Agriculture, 2022)
This study assessed gender differences in the use of climate-smart agriculture among bean farmers in Tanzania. Descriptive and multivariate probit models were used to analyse data collected from 357 randomly selected bean farmers from Mbeya Rural and Mbozi districts. Results revealed gender differences in farmers' vulnerability to production shocks, with higher frequencies of women and young farmers reporting climate change-related constraints than men. Adverse effects of climate change were more pronounced and gender-differentiated at the production level than at post-harvest and marketing levels where significantly more women and young farmers were more affected than men. Men dominated climate-adaptation decision-making processes at the household level because of their ownership and control over access to land, and access to agricultural support services. Enhancing inclusive gender access to land and group-based approaches to information dissemination would be relevant in enabling men, women and young farmers effectively respond to the effects of climate change.